Determinação do consumo de água de planta ananicante de limão Tahiti por lisímetro de pesagem - Nogueira, Vitor Fernando (Universidade Federal de São Carlos, 2025)
This study quantified the water demand of dwarfing 'Tahiti' lime plants (Citrus latifolia Tanaka) grafted onto IAC 10/152 rootstock, using weighing lysimetry in a protected environment. The experiment, conducted in Araras-SP (2020–2024), monitored biometric parameters (height, canopy projection area) and agrometeorological variables, correlating them with crop evapotranspiration (ETc) and the crop coefficient (Kc). The results indicated an average water consumption of 139.30 mm, with peaks of up to 1,077.91 mm during the productive phase, and an exponential relationship between canopy area and ETc (R² = 0.853). The average Kc was 0.60, varying seasonally: minimum (0.21–0.31) during the initial stage/winter and maximum (>1.0, reaching 1.66) at maturation/spring-summer. Vegetative growth proved sensitive to climatic seasonality, with greater development at temperatures >23°C and high solar radiation (23–35 MJ), while winters with significant thermal amplitude (3–37.4°C) reduced the growth rate. It is concluded that the irrigation management of dwarfing 'Tahiti' lime should consider canopy expansion and phenological variations for water optimization, with Kc adjustable according to the phenological stage.
Determination of water consumption from Tahiti lemon dwarf plant by weighing lysimetry
Keywords: Consumo de água; Evapotranspiração; Manejo de irrigação; Gotejamento; Citricultura; Water consumption; Evapotranspiration; Irrigation management; Drip irrigation; Citrus cultivation; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA